Philocalic Sol: Love (Be You)-tifully - Visagie, Pejamauro (Open Mic: A Creative Writing Journal, 2024)
I am air. An heir to be…Pollination and legacy, you see.If you are inclined to read between the lines,then you will be all you can, Bee.Be-You... to full-on become,Evermore beautiful.